De novo genome assemblies of two cryptodiran turtles with ZZ/ZW and XX/XY sex chromosomes provide insights into patterns of genome reshuffling and uncover novel 3D genome folding in amniotes - Bista, Basanta; González-Rodelas, Laura; Álvarez-González, Lucía; Wu, Zhi-qiang; Montiel, Eugenia E.; Lee, Ling Sze; Badenhorst, Daleen B.; Radhakrishnan, Srihari; Literman, Robert; Navarro-Dominguez, Beatriz; Iverson, John B.; Orozco-Arias, Simon; et al. (Genome Research, 2024)
Understanding the evolution of chromatin conformation among species is fundamental to elucidate the architecture and plasticity of genomes. Nonrandom interactions of linearly distant loci regulate gene function in species-specific patterns, affecting genome function, evolution, and, ultimately, speciation. Yet, data from nonmodel organisms are scarce. To capture the macroevolutionary diversity of vertebrate chromatin conformation, here we generate de novo genome assemblies for two cryptodiran (hidden-neck) turtles via Illumina sequencing, chromosome conformation capture, and RNA-seq: Apalone spinifera (ZZ/ZW, 2n = 66) and Staurotypus triporcatus (XX/XY, 2n = 54). We detected differences in the three-dimensional (3D) chromatin structure in turtles compared to other amniotes beyond the fusion/fission events detected in the linear genomes. Namely, whole-genome comparisons revealed distinct trends of chromosome rearrangements in turtles: (1) a low rate of genome reshuffling in Apalone (Trionychidae) whose karyotype is highly conserved when compared to chicken (likely ancestral for turtles), and (2) a moderate rate of fusions/fissions in Staurotypus (Kinosternidae) and Trachemys scripta (Emydidae). Furthermore, we identified a chromosome folding pattern that enables “centromere–telomere interactions” previously undetected in turtles. The combined turtle pattern of “centromere–telomere interactions” (discovered here) plus “centromere clustering” (previously reported in sauropsids) is novel for amniotes and it counters previous hypotheses about amniote 3D chromatin structure. We hypothesize that the divergent pattern found in turtles originated from an amniote ancestral state defined by a nuclear configuration with extensive associations among microchromosomes that were preserved upon the reshuffling of the linear genome.